Taxonomic revision of the Afrotropical Phytomia Guérin-Méneville (Diptera: Syrphidae) - de Meyer, Marc; Goergen, Georg; Jordaens, Kurt (Zootaxa, 2020)
The Afrotropical representatives of the hoverfly genus Phytomia Guérin-Méneville (Diptera) are revised. In total, 19 species are recognized of which three are new to science: Phytomia austeni sp. nov., P. memnon sp. nov., and P. pallida sp. nov. Phytomia neavei Bezzi is considered a junior synonym of P. kroeberi (Bezzi), P. noctilio Speiser a junior synonym of P. pubipennis Bezzi, and P. ephippium Bezzi a junior synonym of P. melas (Bezzi). Lectotypes are designated for the following species: Megaspis bulligera Austen, Megaspis erratica Bezzi, and Megaspis poensis Bezzi. In addition, unpublished lectotype designations are hereby formally published for the following species: Megaspis bullata Loew, Megaspis curta Loew, and Megaspis capito Loew. Phytomia curta (Loew) is considered a valid species, and differentiated from P. natalensis (Macquart). Phytomia fronto Loew is tentatively considered to belong to the genus Simoides Loew. The relationship between the different Phytomia species, as well as the relationship between Phytomia and Simoides, is briefly discussed based on morphological and DNA data.